Norm Comparison Estimates for the Composite Operator. (30th March 2014) - Li, Xuexin; Wang, Yong; Xing, Yuming
Abstract : This paper obtains the Lipschitz and BMO norm estimates for the composite operator𝕄 s ∘ P applied to differential forms. Here, 𝕄 s is the Hardy-Littlewood maximal operator, andP is the potential operator. As applications, we obtain the norm estimates for the Jacobian subdeterminant and the generalized solution of the quasilinear elliptic equation.